MATHEMATICAL STRUCTURES IN THE MOVEMENTS AND FORMATIONS OF THE SELENDANG PEMALANG DANCE: AN ETHNOMATHEMATICAL STUDY - Shofa Hidayat; Naf'a Rohmaniyya; Utiya Nur Arimbi; Muthia Isna Arofah; Faridh Ricky Fahmy (Tadris Matematika, 2026)
This study explores the mathematical structures embedded in the movements, floor patterns, body postures, rhythmic organization, and scarf use of the Selendang Pemalang Dance. A qualitative descriptive design with an ethnographic orientation was employed. Data were obtained from an in-depth interview with a dance practitioner on 3 November 2025, visual observation of three performance videos, and relevant literature. The data were reduced, displayed in a movement-mathematics matrix, and interpreted through the ethnomathematical framework; credibility was strengthened through method and visual-source triangulation. The findings reveal horizontal, parallel, and curved lines; rectangles, parallelograms, trapezoids, scalene and right triangles, rhombi, and semicircles; vertical reflection; and acute, right, obtuse, and straight angles. These forms are not isolated geometric objects but emerge through coordinated spacing, bodily direction, and scarf trajectories. The study's novelty lies in integrating movement, formation, rhythm, and the scarf as one cultural-mathematical system and translating the findings into concrete classroom tasks involving coordinate geometry, polygon classification, transformation, and angle measurement. Selendang Pemalang Dance therefore offers a culturally meaningful resource for contextual mathematics learning and local heritage appreciation.